Factors Determining Choice of Sporting Activities Among Undergraduates in University of Ilorin, Nigeria - Adeyemi, Olalekan; Olaoye, Ayobami K.; Ikwuka, Franca (NIU Journal of Humanities, 2017)
Participating in sports is expected of everyone both male and female, this study examined factors determining choice of sporting activities among undergraduate in University of Ilorin. Students’ choice of sporting activities is predetermined by availability of facilities, peer group, religion and cultural belief, injury, gender, interest among others. The research adopted descriptive survey method. The population of the study comprised all undergraduate in University of Ilorin. Multi-stage sampling technique was used to select 234 respondents. The research instrument used was a researcher’s developed Questionnaire. Chi-square (χ 2 ) was used to test the postulated hypotheses at 0.05 level of significance. The result of the study showed that: Availability of facilities, gender, body somatotype, religious belief determining choice of sporting activities among undergraduate in University of Ilorin. It was recommended that: All sport facilities should be made available and accessible to students, coaches and other related agencies through motivation and regular training should make sure that female students are encourage to participate in sports, students should be trained to have the skill related fitness component such as agility, power, speed, balance, coordination and so on in order to augment their physical characteristics in any sporting activities of their choice. Religious leaders should encourage participation in all sporting activities either team or individual sports. Keywords: facilities, peer group, religion and Injury